Optimization of ultrasound, vanillin and pomegranate extract treatment for shelf-stable unpasteurized strawberry juice. (October 2016) - Tomadoni, B.; Cassani, L.; Ponce, A.; Moreira, M.R.; Agüero, M.V.
Abstract: Optimum combination of ultrasound, vanillin and pomegranate extract to improve quality of strawberry juice was determined using response surface methodology. Samples were stored at 5 °C for 14 days. The optimal conditions to simultaneously minimize native microflora, maximize nutritional parameters and minimize the impact on sensory quality resulted in: 7.5 min of ultrasound treatment, pomegranate extract concentration of 360 μg/mL and vanillin concentration of 0.925 mg/mL. A new batch of strawberry juice was treated at these optimal conditions and stored for validation of the optimization and to evaluate the performance of the optimum treatment on quality parameters throughout storage. Furthermore, a second batch of juice was inoculated with Escherichia coli O157:H7 and processed at optimal conditions to evaluate the effectiveness of the treatment on the pathogen survival. The native microflora of the juice, as well as inoculated pathogen, decreased significantly using the proposed hurdle technologies, with no impact on sensory parameters. Ascorbic acid retention was slightly decreased by the optimum treatment; however, DPPH and polyphenolic compounds were significantly higher than those in untreated sample. Overall, a combination of ultrasound, vanillin and pomegranate extract showed interesting potential to enhance quality and safety of strawberry juice, extending the shelf-life of the product. Highlights: Strawberry juices (SJ) were treated with ultrasound, vanillin and pomegranate extract. An optimum treatment (OT) was obtained through response surface methodology. OT was applied to SJ to evaluate nutritional, sensory and microbial quality through storage. OT was also tested against Escherichia coli inoculated in SJ. OT significantly reduced microflora of SJ without affecting its sensory parameters.